Enhancing Islamic Education Pedagogy within the Full day School System through interactive learning: A Quality Improvement Approach - Elihami, Elihami; Lin, Ming; Biqing, Chang (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
To improve the standard of teaching Islamic Religious Education in the Ajatappareng Region, Indonesia, a thorough review of the recently introduced full-day school system was conducted over two semesters. The purpose of this study was to evaluate the impact of the full-day education system on students’ learning outcomes in Islamic religious studies and to assess the effectiveness of fostering Islamic cultural values. Students from public primary schools in the Ajatapareng area participated in this study, which considered both formal and informal education pathways. The research method used tests, observation, documentation, and both quantitative and qualitative methodologies. The results showed that for primary school children, it is essential to initiate an integrated strategy based on Islamic principles to efficiently achieve the educational goals set by the school. The implications for this study can support independent learning and future programmers in learning design and development at the primary school level.